Loran-C Coordinate Converters - Plague or Panacea - Gray, David H.; Mortimer, Tony (The International Hydrographic Review, 2015)
The advent of Loran-C as the major radio navigation system for North America and the advancement of the electronic technology have resulted in economically viable conversion of hyperbolic readings to geographic coordinates. Although the user will appreciate such extras as : way points, course and speed made good, and track plotter, he should also be aware o f the systematic errors that affect the coordinate conversion. The paper highlights these pro’s and con’s and the progress being made to set minimum performance standards for such converters.